Using GO supporting catalyst to convert biomass into DFF - Li, Haopeng (2018)
Graphene, a two dimensional nanomaterial developed in recent years, has excellent physical and chemical properties. It has been the focus of researchers in recent years. Graphene oxide which as the most important derivative of graphere, because its surface contains a large number of oxygen-containing functional groups, such as hydroxyl, carboxyl and epoxy groups which can greatly promote the water solubility and also provide a possibility for the synthesis of functional graphene, has become a hot spot in the research of catalyst base materials. The functionalization of graphene oxide mainly consists of two types: covalent functionalization and non covalent functionalization. In this paper, two different kinds of catalysts were synthesized by these two methods, and their catalytic properties of biomass conversion were investigated. The biomass is rich, clean and renewable. It will became a good raw material for industrial production in the future. The decomposition of biomass into different substances by high efficiency and cheap catalyst is the guidance of most organic catalysis. In this paper, two different kinds of Catalytic reaction system were prepared for the purpose of producing DFF, and the target products were obtained from using different kinds of biomass as raw materials. In the first part, a highly efficient multifunctional catalytic process is developed to convert cellulose into 2,5-diformylfuran (DFF).In presence of GO@MoO3 as the catalyst and DMSO as the solvent, a remarkable yield of DFF 24.6% is obtained. More importantly, the reaction is performed in open air and under mild conditions. As such, this catalytic system is readily for scale-up production of DFF. In the second part, a catalytic process is developed to convert fructose into 2,5-diformylfuran (DFF). In presence of SGO@Ru as the catalyst and water/toluene as the solvent, a yield of DFF 7.6% is obtained.